A branch current reallocation based energy balancing strategy for the modular multilevel matrix converter operating around equal frequency - Fan, Boran; Wang, Kui; Gu, Chunyang; Wheeler, Patrick; Li, Yongdong (Institute of Electrical and Electronics Engineers, 2018)
Modular multilevel matrix converter (M3C) is a promising topology for medium-voltage high-power applications. Due to the modular structure, it features easy scalability, high quality output waveforms and superior fault tolerance. However, M3C suffers serious capacitor-voltage fluctuation if the output frequency gets closer to the input frequency. This limits its use in the adjustable-speed-drive (ASD) applications. This paper introduces a theoretical analysis in phasor-domain to find the branch energy equilibrium point of M3C when operating around equal frequency. On the basis of this equilibrium point, a branch current reallocation based energy balancing control method is proposed to equalize the energy stored in the nine converter branches. With this novel control method, M3C can effectively overcome the capacitor voltage fluctuation with neither using common voltage nor applying reactive power at the input side.